Synergistic Potentials of Herbal/Phytomedicines - Purohit, Arpana (International Journal of Pharmaceutical & Biological Archive, 2023)
The utilization of herbal medicines and their combination due to synergistic action especially Chinese traditional and Ayurvedic medicines in treating numerous diseases such as cardiovascular diseases, HIV, and cancer has been longstanding since the primordial times and are still in trend. Synergy research in phytomedicine has been acknowledged as a ground-breaking and crucial activity that is demarcated as the interaction between two or additional agents in order to yield a mutual superior outcome which is larger than the summation of their discrete effects.